Role of Self-Efficacy and Negative Perfectionism in the Prediction of Procrastination of Narcissistic Personality: A Study on Non-Clinical Subjects - Hamed Jabbari Ghazi Jahani; Azadeh Ehsanikenari; Afsaneh Sadat Sharif (Emerging Science Journal, 2018)
The present research was performed to investigate the role of self-efficacy and negative perfectionism in the prediction of procrastination of narcissistic personality. This is a descriptive research of correlational type for which performance a total of 412 students were selected via random multi-stage sampling method. In order to examine the research hypothesis and accomplish the research objective, the participants were provided with a questionnaire composed of Narcissistic Personality Inventory-16, General Procrastination Scale, General Self-Efficacy Scale, and Positive and Negative Perfectionism Scale. Collected data were analysed using descriptive statistics, Pearson’s correlation coefficient, and stepwise multiple regression. Results of the research indicated significant associations between self-efficacy, negative perfectionism, and narcissism, in one hand, and procrastination, on the other hand, so that, as variables, self-efficacy, negative perfectionism, and narcissism could explain 10% of the variance in procrastination. Results of the present research indicated the importance of self-efficacy, negative perfectionism, and narcissism in the development and exacerbation of procrastination, and placed an emphasis on the necessity of paying attention to the role of such effective antecedents by mental health-related authorities, so as to reduce procrastination.